KUALITAS PELAYANAN KEPOLISIAN PADA SATUAN RESERSE KRIMINAL POLRES SUMEDANG - Drupada, Oktavia (JRPA - Journal of Regional Public Administration, 2025)
This researcher aims to determine the Quality of Police Services at the Sumedang Police Criminal Investigation Unit. The quality of police services provided is handling reports of criminal cases from the public. This research was conducted using a qualitative method. Data collection techniques were carried out through literature studies and field studies which included: observation, interviews, documentation studies, and triangulation. Determination of samples/informants in this study was carried out using purposive sampling, namely 4 people. While the data processing procedure used the Miles and Huberman data analysis model. The final results of the study showed that overall, the quality of police services at the Sumedang Police Criminal Investigation Unit in providing services to the public in terms of tangible, reliability, responsiveness, assurance, and empathy can be said to have been running quite well. When conducting the research, the researcher found problems related to the scattering of important documents in each room that had not been properly arranged. Suggestions from the researcher include optimizing air conditioning facilities in each unit such as air conditioners and fans, providing explanations that are easy for the public to understand regarding the procedures and mechanisms of investigations and investigations that are not state secrets.